Idarucizumab for dabigatran overdose. (13th September 2016) - Peetermans, Marijke; Pollack, Charles; Reilly, Paul; Liesenborghs, Laurens; Jacquemin, Marc; Levy, Jerrold H.; Weitz, Jeffrey I.; Verhamme, Peter
Abstract: Context: An overdose of oral anticoagulants represents a challenging scenario for emergency physicians. Dabigatran, an oral direct thrombin inhibitor, is increasingly used in place of warfarin. The lack of an antidote is a concern in patients who overdose on dabigatran, even though the drug can be eliminated with hemodialysis. Idarucizumab is an antibody fragment that binds dabigatran with high affinity. It reverses the anticoagulant effect of dabigatran within minutes and is approved for the reversal of dabigatran during emergency situations. Case details: We describe the use of idarucizumab in the management of a 68-year-old woman who was taking dabigatran 150 mg twice daily and ingested 125 capsules. Despite gastric lavage and administration of activated charcoal within two hours of drug intake, the activated partial thromboplastin time (aPTT) and prothrombin time (PT) remained prolonged. The administration of 5 g of intravenous idarucizumab promptly and completely reversed the anticoagulant activity of dabigatran as assessed by routine and specific coagulation assays (aPTT from to 75 to 26 s, PT from 26 to 11 s and diluted thrombin time from 92 to 27 s). The initially planned emergency hemodialysis was canceled. Discussion: This case highlights the potential use of idarucizumab for the management of massive dabigatran overdoses.